Sub/super‐synchronous harmonics measurement method based on PMUs. Issue 13 (12th December 2017) - Liu, Hao; Xu, Sudi; Bi, Tianshu; Cao, Chuang
Abstract : In recent years, there are more and more inter‐harmonics in power system, with the rapid development of new energy and the application of the quantity power electronic equipment in power grid. These lead to the sub‐synchronous oscillation having a negative effect on the stable of power grid. Nowadays, phasor measurement units (PMUs) are deployed in the power system in large quantities, which provides a possibility to monitor the inter‐harmonics in grid. In this paper, a reduction method of sub/super‐synchronous harmonics based on PMU phasor data is proposed. To decompose the sub/super‐synchronous harmonics, first spectrum analysis on complex phasor sequences should be done. Second, an idea is proposed that calculates the frequency and amplitude of inter‐harmonics separately. That is to say, the frequency can be got by spectrum analysis while zero‐padding in short time window, and the amplitude can be calculated by solving equations. This can overcome the shortcoming of spectrum analysis which has larger amplitude error. Simulation and experimental tests show that the frequency and amplitude of inter‐harmonics can be calculated using the proposed algorithm.